1996
DOI: 10.1159/000289054
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive-Behavioral Self-Help Educational Program for Patients with COPD

Abstract: Background: The purpose of this pilot study was to evaluate the impact of an 8-week cognitive-behavioral self-help educational program for individuals with COPD on level of disability. Methods: Eight adults ranging in age from 58 to 83 years attended a program that included a cognitive-behavioral intervention strategy. Levels of disability, cognitive distortion, anxiety, depression, somatic symptoms, and hostility were measured pre- and posttreatment using the Sickness Impact Profile, two Cognitive Error Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 19 publications
0
37
0
4
Order By: Relevance
“…Five previous controlled trials have provided evidence that CBT can decrease anxiety symptoms in COPD patients who have not been selected on the basis of existing psychopathology [11][12][13][14][15]. However, in all five studies, anxiety symptoms were measured solely by self-report questionnaire and only one of the studies included a follow-up assessment (at 3 months) [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five previous controlled trials have provided evidence that CBT can decrease anxiety symptoms in COPD patients who have not been selected on the basis of existing psychopathology [11][12][13][14][15]. However, in all five studies, anxiety symptoms were measured solely by self-report questionnaire and only one of the studies included a follow-up assessment (at 3 months) [12].…”
Section: Discussionmentioning
confidence: 99%
“…The results of several controlled trials using self-report questionnaires have indicated that CBT can decrease anxiety symptoms in patients with COPD; however, the effects of CBT on panic attacks and the development of panic disorder in COPD have not been assessed [11][12][13][14][15]. Intervening early with individuals at risk of panic disorder can prevent the personal and economic effects of the disorder becoming entrenched [16].…”
mentioning
confidence: 99%
“…Results from the neuro-psychological tests showed that the memory of these patients is damaged, which impedes the evocation of verbal and non-verbal information, making it difficult to remember the lessons, and recognition of the studied material 11 . Cognitive development has particular relevance in populations suffering from COPD, because research shows that the cognitive deficits of patients with hypoxemia contribute to a lower quality of life due to mental confusion and memory problems 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Lisansky et al 12 studied cognition, anxiety, depression, somatic symptoms, hostility and inaptitude disturbances in patients suffering from COPD by means of an educational and self-care program, with initial and final interventions.…”
Section: Discussionmentioning
confidence: 99%
“…La clasificación de los sujetos en función de sus alteraciones ansiosas y depresivas nos da una indicación de la alta prevalencia de éstas, y nos permite apreciar cómo aumenta cuando se produce una descompensación del cuadro. Además, estos datos nos remiten a los existentes en la bibliografía en torno a las importantes manifestaciones ansiosas y depresivas que aparecen en los enfermos con EPOC (Anderson, 1995;Araúxo, Sureda y Pablo, 1997;Creer, 1983;Lisansky y Clough, 1996;Quirk y Jones, 1995;Van Elderen, 1995). Así, los trabajos previos no sólo nos informan de la alta prevalencia en estos enfermos sino también de las diferencias que existen entre los síntomas depresivos y ansiosos, con una mayor presencia de aquellos.…”
Section: Discussionunclassified